2019
DOI: 10.1038/s41419-019-1918-1
|View full text |Cite
|
Sign up to set email alerts
|

Lobaplatin promotes 125I-induced apoptosis and inhibition of proliferation in hepatocellular carcinoma by upregulating PERK-eIF2α-ATF4-CHOP pathway

Abstract: We investigated the mechanism underlying the effect of a combination treatment of 125I radioactive seed implantation and lobaplatin (LBP) in hepatocellular carcinoma. The effects of administration of HCC cells and subcutaneous tumor model of mice with different doses of 125I or a sensitizing concentration of LBP alone, or in combination, on cellular apoptosis and proliferation were analyzed and it was confirmed that LBP promotes 125I-induced apoptosis and inhibition of proliferation of HCC. Furthermore, isobar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…From our previous study, we saw that 125 I could induce cellular apoptosis and cell cycle arrest in PANC-1 cells; 21 moreover, another recent study on HCC demonstrated that LBP promoted 125 I-induced apoptosis and anti-proliferative effect via the PERK-eIF2α-ATF4-CHOP pathway, which we identified by iTraq. 20 In our present study, we verified that 125 I could significantly inhibit tumor growth in vivo and decrease proliferation with G2/M cell cycle arrest in vitro; interestingly, these anticancer effects could be enhanced by LBP.…”
Section: Oncotargets Andsupporting
confidence: 72%
See 4 more Smart Citations
“…From our previous study, we saw that 125 I could induce cellular apoptosis and cell cycle arrest in PANC-1 cells; 21 moreover, another recent study on HCC demonstrated that LBP promoted 125 I-induced apoptosis and anti-proliferative effect via the PERK-eIF2α-ATF4-CHOP pathway, which we identified by iTraq. 20 In our present study, we verified that 125 I could significantly inhibit tumor growth in vivo and decrease proliferation with G2/M cell cycle arrest in vitro; interestingly, these anticancer effects could be enhanced by LBP.…”
Section: Oncotargets Andsupporting
confidence: 72%
“…Our previous research indicated that 125 I induced apoptosis and proliferation inhibition in HCC by upregulating the PERK-eIF2α-ATF4-CHOP pathway. 20 Based on our previous iTraq results, we found that the function of 125 I is related to the AKT/mTOR pathway. In this study, we explored whether LBP could sensitize A549 cells to 125 I radiation and determined the potential links among 125 I, LBP, and the AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations